Improvement Measures for Waterlogging Prevention and Control Standards of Highly Built-up Areas - ZHANG Xiaoju; REN Dawei (Renmin Zhujiang)
For highly built-up urban areas,further improving the waterlogging prevention and control standards and refining the waterlogging prevention and control system with a limited land use space are problems demanding prompt investigation.Taking Shenzhen's improvement strategies for waterlogging prevention and control standards as an example,this paper analyzed the main points and applicability of several measures,including source optimization,vertical adjustment,improvement of pipe network standards,multi-aspect drainage system,diversified detention measures,and joint control of flood and waterlogging.By investigating representative basins,this paper also built a Mike Flood model to evaluate the effects of different waterlogging prevention and control schemes.The results show that an 85% reduction of waterlogging risk areas can be achieved by comprehensively applying the waterlogging prevention and control measures according to local conditions under a once-in-a-hundred-year rainstorm,indicating the efficacy of those measures.The results provide a reference for cities to develop improvement strategies for waterlogging prevention and control standards under similar conditions.